IOT BASED HOUSEHOLD ELECTRICITY ENERGY MONITORING AND CONTROL - Salisu, Abubakar; Bugaje, Aminu; Loko, A. Z. (FUDMA JOURNAL OF SCIENCES, 2021)
Internet of Things (loT) has opened up a myriad of applications in many areas, including medical and healthcare networks, smart home control, and environmental surveillance. IoT is supposed to bring about a large amount of progress in the ubiquitous computing sector. IoT-based energy management programs may allow a significant contribution to energy conservation. Therefore, this paper focuses on the design and implementation of an IoT based household electricity energy monitoring and electric bulb remote control for the reduction of electrical wastage using ESP 32-bit microcontroller. The ESP 32 microcontroller was used as the brain of the entire system which processes the energy consumption, temperature reading. Temperature monitoring can assist tremendously in the explosion and burning incidence avoidance, thereby saving lives and properties. The ESP32 microcontroller also handles the internet connectivity via its inbuilt WIFI module in order to transmit the real-time energy consumption, temperature reading, and electric bulb remote control over the internet. A MATLAB app was designed to serve as user interface for monitoring the household electricity energy consumption, temperature reading and electric bulb remote control via Thingspeak cloud server from MathWorks (makers of MATLAB) and also monitors the temperature and electricity consumed by the pressing iron and the hair dryer. Whenever, the electricity consumption or temperature reading exceeds the set threshold on the MATLAB app, a notification is sent to the user’s Email. The system could be used for reducing the wastage of electrical energy in the house by proper scheduling and monitoring of the appliances